Application of Taguchi Experimental Design in Optimization of Levulinic Acid Production from Cellulose Derived From Millet Stalk - Ibrahim, Shehu; Muhammad, Abdullahi Sokoto; Umar, Kabiru Jega; Muhammad, Ibrahim Magami (Biology, Medicine, & Natural Product Chemistry, 2024)
Cellulose is the primary component of lignocellulosic biomass and the main source of renewable materials in chemical industry. This study aims at optimizing the production of levulinic acid from cellulose derived from millet stalk using Taguchi experimental design approach. The millet stalks were pretreated by acid and alkali treatment method. The extractives, hemicellulose, lignin, and cellulose contents of the millet stalks were estimated using dry-weight basis technique. Levulinic acid production from the millet stalk was carried out in Teflon lined stainless steel autoclave (50cm3) using standard method. The optimum conditions for the production of levulinic acid were evaluated using Taguchi experimental design method. Levulinic acid was characterized using GC-MS and FT-IR techniques. The cellulose content of the millet stalk was significantly (p < 0.05) higher than the other components. FT-IR spectrum showed the presence of O-H, C=O, C-H, and C-O stretch in the levulinic acid. The highest (95%) yield of the levulinic acid was obtained with an acid concentration of 0.2M at 2000C, for 4 hours. The optimum temperature, acid concentration, and time for the production of levulinic acid from the millet stalk were 2000C, 0.2M, and 4 hours, respectively. Levulinic acid is characterized by a range of functional groups.Keywords: Cellulose, Levulinic acid, Millet stalk, Optimization, Taguchi design